A Path Analysis Model of Protection and Risk Factors for University Academic Stress: Analysis and Psychoeducational Implications for the COVID-19 Emergency - de la Fuente, Jesús (Frontiers in Psychology, 2021)
The aim of this research was to empirically validate hypothesized predictive relationships of protection and risk factors for experiencing academic stress. A synthesis of models –the Presage-Process-Product model; Studying, Learning and Performing under Stress competency model; and Self- vs External- Regulatory Theory—underlie the investigation and are important for assessment and guidance in stress situations within the university context. Over the course of an academic year, a sample of 564 Spanish university students voluntarily completed validated questionnaires, in an online format, on several psychological variables connected to academic stress. Correlational analysis and Path Analysis Model, within an ex post facto design, were used to build empirical models of the presage-process-product factors that constitute protection or risk factors for academic stress Two statistically acceptable models appeared: one with protection factors and another with risk factors for predicting and preventing academic stress at university. These results support the need for Psychology Units at university that have a preventive, health and education focus, going beyond the merely clinical. Focus on the individual is insufficient, given that there are also contextual factors that predispose academic stress. Discussion, conclusions and implications for assessment and intervention in academic stress in university students and teachers, within the present COVID-19 crisis, are offered.